Reconciliation of work and family life in Hungary - RECWOWE; Duman, Anil; Horvath, Anna (Edinburgh, 2010)
"The paper analyses the ‘Europeanization’ of policies concerning the reconciliation of work and family life in Hungary between 1998 and 2005. It looks at how politicians – in government or in the opposition – framed European requirements and/or standards and how they used references to European processes in their arguments. The paper distinguished three periods of Europeanization. In the first period – in which the first comprehensive Family Support Act was adopted – basically no reference was made to the European Union. Accordingly, this Act – its goal being to protect the institution of the family to ensure demographic growth – did not prioritize reconciliation and women’ employment at all and was criticized of not being in line with European principles. The second period before 2004 was the period of legal harmonization. Therefore, reconciliation-related acts (e.g. on telework) were mainly adopted as an answer to European expectations. Finally, in the third period after the 2004 accession, the reconciliation of work and family life became an explicit goal of the government, usually with references made to European processes and European principles. In this period, MPs started using the jargon of the EU. Furthermore, the availability of European funding was an important trigger of reconciliation-related reforms."